PENGARUH DEBT TO EQUITY RATIO, INVENTORY TURNOVER, TOTAL ASSETS TURNOVER DAN FIRM SIZE TERHADAP PROFITABILITAS PADA PERUSAHAAN REAL ESTATE DAN PROPERTY YANG TERDAFTAR DI BURSA EFEK INDONESIA - Setyaningsih Sri Utami, Indah Kusuma Wardani, Suprihatmi Sri Wardiningsih & (Universitas Slamet Riyadi, 2016)
This research aimed to analyze: (1) the significant effect of Debt To Equity Ratio on Return On Asset; (2) the significant effect of Inventory Turnover on Return On Asset; (3) the significant effect of Total Asset Turnover on Return On Asset; and (4) the significant effect of Firm Size on Return On Asset.This research took object in Indonesia Stock Exchange in Real Estate and Property companies presenting financial statement for 2011-2014 period and yielding profit during 2011-2014 period. This study was a secondary research; technique of collecting data used was documentation study on financial statement for 2011-2014 period. The method of analyzing data used was regression prerequisite test using classical assumption test, multiple linear regression analysis, and coefficient of determinacy test, while hypothesis testing was carried out using t-test and F-test. Considering the classical assumption test, it could be seen that the data of research variable had meet the required assumption in multiple linear regression model, in which there was no multicolinearity problem, autocorrelation, heteroscedasticity and normal residual. Based on t-test, it could be found that only Inventory Turnover indicated insignificant result. The size of independent variable’s contribution to independent variable was 41%. The conclusion of each hypothesis testing result showed that (1) Debt to Equity Ratio affected significantly Return On Asset in Real Estate and Property company during 2011-2014, yielding p value 0.000 < 0.05. Thus, hypothesis 1 was supported; (2) inventory turnover ratio did not affect significantly the Return On Asset in Real Estate and Property company during 2011-2014, yielding p value 0.745 > 0.05; thus, hypothesis 2 was not supported; (3) Total Asset Turnover ration affected significantly Return On Asset in Real Estate and Property company during 2011-2014, yielding p value 0.000 < 0.05; thus hypothesis 3 was supported; (4) firm size affected significantly Return On Asset in Real Estate and Property company during 2011-2014, yielding p value0,002 < 0,05; thus hypothesis 4 was supported.Keywords: debt to equity ratio, inventory turnover, total asset turnover, firm size, return on asset.